Unsur Female Gaze dalam Narasi Game “Mouthwashing” - Rahyanninta Ilma; Irma Damajanti; Kiki Rizky Soetisna Putri (Fakultas Desain Universitas Komputer Indonesia, 2025)
“Mouthwashing” is a game that has achieved many prestigious awards and nominations just within a few months after its’ release on 24th September 2024. This horror game was conceptualized and written by Johanna Kasurinen which then got developed to a game by Wrong Organ Studio. While it’s nothing new, it’s still rare to find a female game creator and even rarer is when a game made by women has achieved as many awards as “Mouthwashing” had. This research is a critical reading of the female role in the game “Mouthwashing” and how a female’s view is applied in her works. This is qualitative research with the data taken from a game playthrough video and interview articles with Kasurinen. The main theory used for this research is the female gaze theory by Laura Mulvey. In the game, there’s only one female character named Anya whose role is quite significant both in gameplay function and the overall theme. Kasurinen herself had stated in interviews that she often looks back upon herself while writing characters that aren’t only not good, but also human. In conclusion, despite the strong female gaze aspect, the narration of the overall game doesn’t fit into the feminist category.